A unified approach to sensitivity and specificity evaluation of novel potential fluorescent dye probes for proteins - Okladnoy, Yu.G.; Dyubko, T.S. (Functional Materials, 2005)
The existing evaluation criteria of novel fluorescent dyes proposed as potential fluorescent probes for proteins have been considered and a method has been proposed to unify the approach to the sensitivity and specificity evaluation of a new dye at interaction with a protein. The conditions of the evaluation applicability to the property selection and comparison for novel dyes proposed as potential fluorescent probes are analysed. Рассмотрены существующие критерии оценки свойств новых флуоресцентных красителей, предлагаемых в качестве потенциальных флуоресцентных зондов для белков, и предложен способ унификации подхода к оценке чувствительности и специфичности новых красителей при взаимодействии с белком. Анализируются условия применимости данной оценки при отборе и сравнении свойств новых красителей, предлагаемых в качестве потенциальных флуоресцентных зондов. Розглянуто iснуючi критерiї оцiнки властивостей нових флуоресцентних барвникiв, якi пропонуються в якостi потенцiйних флуоресцентних зондiв для бiлкiв, i запропоновано спосiб унiфiкацiї пiдходу до оцiнки чутливостi i специфiчностi нових барвникiв при взаємодiї з бiлком. Аналiзуються умови застосування даної оцiнки при вiдборi i порiвняннi властивостей нових барвникiв, якi пропонуються в якостi потенцiйних флуоресцентних зондiв.